2019
DOI: 10.3390/diagnostics9020047
|View full text |Cite
|
Sign up to set email alerts
|

Health Predictors of Pain in Elderly—A Serbian Population-Based Study

Abstract: Objectives: The aim of our study was to evaluate the association of health factors with the presence and different degrees of pain in elderly above 65 years of life. Methods: The population-based study included 3540 individuals above 65 years of age of life from twofold stratified household sample representative for Serbia, during 2013 (the average age 73.9 ± 6.3 years; average Body Mass Index was 26.7 ± 4.4, females 56.8%, living with partner 55.5%, with primary education 55.3%, with poor wealth index 55.8% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Consequently, no definite causal inferences can be drawn with regard to the variables under study. Nonetheless, the hypothetical research model of this study is based on theoretically well-established QoL models (Lawton, 1983; Veenhoven, 2000) and empirically justified (compare Adams et al, 2016; Ben-Zur, 2016; Bowling et al, 2002; Cohen-Mansfield & Taylor, 1998; Cramer-Ebner et al, 2017; Frieswijk et al, 2007; Helvik et al, 2013; Ingrand et al, 2018; Jonker et al, 2008; Kostadinovic et al, 2019; Leão & Perelman, 2018; Li et al, 2006; Naughton et al, 2016; Song et al, 2018; Steptoe et al, 2015; Trentini et al, 2012; Tse et al, 2012; Wiesmann & Hannich, 2014). Furthermore, the longitudinal design permitted unobserved heterogeneity to be controlled for (compare Giesselmann & Windzio, 2012; Pforr & Schröder, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, no definite causal inferences can be drawn with regard to the variables under study. Nonetheless, the hypothetical research model of this study is based on theoretically well-established QoL models (Lawton, 1983; Veenhoven, 2000) and empirically justified (compare Adams et al, 2016; Ben-Zur, 2016; Bowling et al, 2002; Cohen-Mansfield & Taylor, 1998; Cramer-Ebner et al, 2017; Frieswijk et al, 2007; Helvik et al, 2013; Ingrand et al, 2018; Jonker et al, 2008; Kostadinovic et al, 2019; Leão & Perelman, 2018; Li et al, 2006; Naughton et al, 2016; Song et al, 2018; Steptoe et al, 2015; Trentini et al, 2012; Tse et al, 2012; Wiesmann & Hannich, 2014). Furthermore, the longitudinal design permitted unobserved heterogeneity to be controlled for (compare Giesselmann & Windzio, 2012; Pforr & Schröder, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, objective QoL indicators have been found to be associated with self-perceptions of health: It has been shown that health problems in terms of chronic conditions and functional impairments predict worse self-rated health and more severe pain, and are related to worse health comparisons (Kostadinovic et al, 2019; Leão & Perelman, 2018; Li et al, 2006; Song et al, 2018).…”
Section: The Role Of Self-perceptions Of Health In Geriatric Rehabili...mentioning
confidence: 99%
See 2 more Smart Citations